Understanding HIV-Related Stigma Experienced by Mothers: The Next Generation and Implications of the New Ontario Health Education Curriculum - Hunter, Linda; LaCroix, Emerson (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
There are many sources of stigma for mothers living with HIV in Canada, and these negatively impact their decision about whether or not to disclose their status. Societal norms and values regarding motherhood are generally not compatible with the negative and stigmatizing messages that exist about HIV-positive women becoming mothers. One reason that many HIV-positive mothers are often unwilling to access health supports is because of the stigma and unwelcomed surveillance that accompany their diagnosis. We begin with a brief discussion on sources of stigma for women and mothers living with HIV, and then move into a discussion on the newly revised Ontario Health Education Curriculum in terms of its progress in addressing HIV-related stigma. Although we note there is room for improvement, the new health curriculum has positive implications for reducing HIV-related stigma by promoting greater awareness around the effects of stigma. Additionally, we propose that HIV-awareness poster campaigns may be a useful tool for supplementing the work of the curriculum in reducing and, ultimately, eliminating HIV- related stigma. The new Ontario Health Education Curriculum, as well as more recent HIV-awareness poster campaigns, challenge the dominant perceptions about HIV stigma, and they have the potential to lead to positive change, which could reduce HIV-related stigma for mothers now and in the future.